Pendekatan kaunseling menangani masalah kebebasan dalam kalangan pelajar institut pengajian tinggi: dua kajian kes - Zainuddin Abu,; Zuria Mahmud,; Salleh Amat, (penerbit ukm, 2008)
This article describes two counseling cases regarding college student problems, focusing on the issue of managing autonomy. Data is obtained through observation, counseling report, and recorded interviews that occurred in five sessions. Data from the interviews was analyzed by listening to the tapes, writing the verbatim and categorizing. This data was compared to the counselor’s written report in order to match the information gathered. Results showed that both clients were not prepared and unable to manage freedom in a matured way, having family conflicts, too dependent on peers and failed to fulfill responsibilities as students. Background information revealed that the clients were not exposed to freedom before college life, having strict and violent fathers, and are middle children. Counseling processes conducted involved assertiveness training and family counseling. The implemented counseling approaches indicated positive results in which the clients regained self confidence, gained insights on family relationships and family support, and developed more effective behaviors.